Casca de arroz como biossorbente para fins analíticos: caracterização físico-química, morfológica e aplicação em leite materno humano - Cardoso, Leonardo Corrêa (2024)
The secretion of drugs and medications in human breast milk has been shown to be important in clinical medicine. Liquid chromatography with a diode array detector is the most popular technique in the literature due to its simplicity and low analysis value, facilitating reproducibility. Chromatographic analyzes have intensified their coupling with various clean up methods, such as QuEChERS, which is simple, fast and cheap for determining pesticide residues in fruits and vegetables, and has become a promising technique for analyzing drugs in various biological matrices. . The adoption of sustainable alternative materials, with a high silica content as a biosorbent in the sample clean-up phase, could reduce environmental impacts. This aimed to develop an analytical method and replace commercial sorbents in the clean up of the QuEChERS methodology with a natural sorbent, in addition to a physicochemical and morphological characterization of this biosorbent for analytical purposes in an unprecedented manner. Thus, commercial sorbents (PSA, C18 and GCB) and biosorbents (orange pomace, passion fruit pomace, cork and rice husk) were screened, to later carry out a chromatographic analysis to select the biosorbents that make up the search. Afterwards, the biosorbent was double characterized, addressing its morphological and physical-chemical aspects. Regarding the first, analysis of particle size polydispersity was carried out using laser light diffraction and scanning electron microscopy (SEM). Finally, moisture, ash and total extractives were analyzed, in addition to determining the concentration of cellulose, hemicellulose and lignin. Furthermore, thermogravimetric analysis, Fourier transform infrared spectroscopy, X-ray diffraction were carried out, the water retention index (WRI), zeta potential, electrophoretic mobility and conductivity were calculated. Based on the results of the initial tests, aiming to obtain an idea of the interactions that occur between the main independent variables that govern the QuEChERS methodology with the use of biosorbents, a central composite rotational design (DCCR) was developed as a next step to verify the interaction and identification of the main independent variables. PSA was elected as the best commercial sorbent and rice husk as the best biosorbent. The rice husk was characterized morphologically and physicochemically and obtained the following results: span (2.567 ± 0.09), [D4.3] (126 ± 27), in SEM the rice husk has a non-uniform pattern in its shape compared to commercial sorbents. Its composition was approximately 27% (cellulose), 13% (hemicellulose), 9% (lignin), 23% (extractives), 20% (ash) and 8% (moisture). The WRI analysis was about 72%, while the zeta potential (-19.2 ± 0.8), electrophoretic mobility (- 1.502 ± 0.06) and conductivity (1.37 ± 0.05). Optimization using DCCR proved to be the best premise for clean up under the following conditions: 8 mg of rice husk, 3.3 minutes of centrifugation at 12,000 RPM and 70 seconds of vortexing. Afterwards, rice husk and PSA were compared with the QuEChERS methodology in the optimized condition, where the assay provided valuable information about the comparative effectiveness of the sorbents in cleaning up extracts.